Implementation of SCM System in Distribution and Stock at Ozan Glass Store - Mufti Hafiz; Nurwati Nurwati; Abdul Karim Syahputra (International Journal of Management Science and Information Technology, 2026)
The increasingly rapid development of the business world requires business actors to be able to manage their operational activities more effectively and efficiently. In this study, problems that often occur at the Ozan Glass Shop, such as the process of managing product and inventory data, which is still carried out simply, so that there is often a discrepancy between stock data and actual conditions. The unintegrated inventory monitoring process also makes it difficult to control stock levels and has the potential to cause shortages or stockpiles of goods. These conditions cause the available information to be less than optimal as a basis for decision making, so that the implementation of a Supply Chain Management (SCM) system is needed to improve the effectiveness of inventory management and product distribution. In addition, through the main discussion carried out in this study aims to be able to understand the process of product distribution from suppliers to the Ozan Glass Shop and its obstacles, determine the implemented stock management and monitoring system and analyze distribution and inventory to improve operational efficiency and reduce problems that occur in the store's business activities. Based on the overall description in this study, the author can conclude that the implementation of the Supply Chain Management (SCM) system at the Ozan Glass Shop has succeeded in improving the effectiveness of inventory management and product distribution. Before the system was implemented, operational processes were still carried out manually, resulting in frequent stock data discrepancies, delays in information, recording errors and difficulties in monitoring order status and distribution. This research resulted in a web-based SCM system capable of integrating stock management, orders, procurement, and distribution within a single platform. Implementation results show that the system can provide real-time inventory information, improve data accuracy, accelerate administrative processes, and facilitate product distribution monitoring. Furthermore, the system is capable of generating more structured and informative reports, supporting faster and more accurate decision-making. The system's implementation also resulted in increased operational efficiency, reduced recording errors, and improved customer service quality.